Impacted wooden toothpick in the stomach - Yahata, Shinsuke; Kamada, Momoka; Kenzaka, Tsuneaki (Clinical case reports, 2018)
Key Clinical Message Foreign body ingestion should be considered when evaluating acute onset epigastric pain, even if patients have no recollection of foreign body ingestion and suspicious conditions or habits, especially in the regions where toothpicks are used on a daily basis. Foreign body ingestion should be considered when evaluating acute onset epigastric pain, even if patients have no recollection of foreign body ingestion and suspicious conditions or habits, especially in the regions where toothpicks are used on a daily basis.